Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.04.08.033035
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress-Induced Transient Cell Cycle Arrest Coordinates Metabolic Resource Allocation to Balance Adaptive Tradeoffs

Abstract: The ability of a cell to mount a robust response to an environmental perturbation is paramount to its survival. While cells deploy a spectrum of specialized counter-measures to deal with stress, a near constant feature of these responses is a down regulation or arrest of the cell cycle. It has been widely assumed that this modulation of the cell cycle is instrumental in facilitating a timely response towards cellular adaptation. Here, we investigate the role of cell cycle arrest in the hyperosmotic shock respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…A previous study reported that under rich-glucose conditions, yeast stored excess carbon in several metabolic pathways, and the first step of the osmotic stress response was to route internal stores of the metabolic flux to glycerol production, accelerating osmoadaptation. 32 However, our results show that metabolic flux redistribution may be more important (data not shown). When glucose was relatively abundant, the growth rate of the cells treated with 0.1% glucose was almost the same as that of the cells treated with 2% glucose.…”
Section: Resultsmentioning
confidence: 53%
“…A previous study reported that under rich-glucose conditions, yeast stored excess carbon in several metabolic pathways, and the first step of the osmotic stress response was to route internal stores of the metabolic flux to glycerol production, accelerating osmoadaptation. 32 However, our results show that metabolic flux redistribution may be more important (data not shown). When glucose was relatively abundant, the growth rate of the cells treated with 0.1% glucose was almost the same as that of the cells treated with 2% glucose.…”
Section: Resultsmentioning
confidence: 53%
“…It is well established that metabolic changes and cell cycle control are bi-directional and osmotic stress has been shown to induce a transient cell cycle arrest in certain organisms. 56 This transient arrest is a counter-measure that mediates short term adaptation in response to stress and allows for a redistribution of the resources needed for survival. In contrast to this, the accumulation of cells at G0/G1 after 24 hours of hyperosmolar culture is most likely due to the higher energy demand required for cells to move into S phase.…”
Section: Discussionmentioning
confidence: 99%
“…All these processes rely on biomolecular rearrangement and volume changes, and as such may impact local macromolecular crowding conditions. Cell growth is often inhibited during stress ( X. Li & Cai, 1999 ; Taïeb et al, 2021 ), correlated to diversion of metabolic resources diverted to mitigate the resultant detrimental physiological effects ( Bonny et al, 2020 ; Chasman et al, 2014 ). Growth capability is therefore a key parameter in measuring cellular recovery, with those that fail to reverse the arrest and re-enter a replicative cycle generally dying ( Petranovic & Ganley, 2014 ).…”
Section: Introductionmentioning
confidence: 99%